The historical reliability of John's gospel : issues & commentary - Blomberg, Craig L., 1955- (Leicester, England, Inter-Varsity Press, 2001)
Craig L. Blomberg offers a foundational introduction and commentary, focusing with intelligence and sure-footed care on the historicity of the Gospel of John.
pt. 1: Introductory considerations --
Includes bibliographical references (pages 295-327) and indexes.
Keywords: Jesus Christ -- Historicity; Bible. -- Criticism, interpretation, etc. -- History; Criticism, interpretation, etc; History